Study of acquired oesophageal strictures - Jaiswal, Nandakishor; Jaiswal, Kirti; Deshpande, Amit V. (International Surgery Journal, 2018)
Background: We profiled the patients of acquired oesophageal strictures coming to our hospital in terms of causes, clinical presentation, efficacy of investigations and treatment modalities. Methods: In this two-year observational study, all patients presenting with complaint of difficulty in swallowing were enrolled and subjected to detailed history taking, examination, barium swallow study and other investigations. The patients were managed with surgical and/or non-surgical approaches, as indicated. Results: Out of total 46 eligible patients, 34 presented with malignant strictures while 12 presented with benign ones. Dysphagia was the commonest symptom in patients with malignant (31, 91.17%) as well as benign strictures (12, 100%). Shouldering with hold up of barium (19, 55.88%) was the most common finding noted in malignant strictures, while those with benign stricture had smooth tapering (7, 58.33%) as the commonest finding. On flexible endoscopy, the level of growth corroborated with the barium swallow findings in all 34 patients with malignant strictures and the lower one third (16, 47.05%) was observed to be the most common site of affection. Majority (21, 58.8%) of patients were having squamous cell carcinoma, with adenocarcinoma dominating in lower one third lesions (13 out of 16, 81.25%). No cases of adenocarcinoma were noted in middle and upper one third lesions. Conclusions: Majority of patients with malignant strictures were having squamous cell carcinoma, with adenocarcinoma dominating in lower one third lesions. Surgical resection led to relief from dysphagia in all the 6 cases of oesophagectomy with oesophagogastric anastomosis in malignant stricture cases with excellent long term survival and symptomatic relief